Music can be trendy and cool - Loureiro, S. M. C.; Ganhão, M.; Guerreiro, J.; Bilro, R.G. (2024 Global Fashion Management Conference at Milan, 2024)
Within the music industry, the topic of fan-related behavior is barely researched, as literature on the music market has mainly focused on piracy (Borja et al., 2015), economic theories on superstars (Coelho & Mendes, 2019), and music information retrieval (Fricke et al., 2018), among others. Hence there is a big research gap related to what makes consumers consistently prefer certain music artists, to the detriment of others, and how the loyalty progressive dynamic works in this industry. What factors influence fan-related behavior in the music industry? Music tone and style can be trendy. Therefore, not only is there a noticeable research gap concerning the factors that make music consumers fans of their preferred artists and the general dynamics of this phenomenon in the industry, but it is also relevant to study the differences in predictors and dynamics between popular and not popular artists that now may attempt to retain music listeners through similar means. The main aim is to explore the factors that influence fan-related behavior toward music artists.